2005
DOI: 10.5194/acp-5-3289-2005
|View full text |Cite
|
Sign up to set email alerts
|

Hydrocarbon-like and oxygenated organic aerosols in Pittsburgh: insights into sources and processes of organic aerosols

Abstract: Abstract.A recently developed algorithm has been applied to deconvolve the mass spectra of organic aerosols acquired with the Aerosol Mass Spectrometer (AMS) in Pittsburgh during September 2002. The results are used here to characterize the mass concentrations, size distributions, and mass spectra of hydrocarbon-like and oxygenated organic aerosol (HOA and OOA, respectively). HOA accounts for 34% of the measured organic aerosol mass and OOA accounts for 66%. The mass concentrations of HOA demonstrate a promin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

109
481
6
5

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 603 publications
(601 citation statements)
references
References 74 publications
109
481
6
5
Order By: Relevance
“…f 60 repre-sents the prevalence of primary combustion products such as levoglucosan and is used as an indicator for fresh BB emissions (Schneider et al, 2006;Alfarra et al, 2007). Conversely, f 44 is associated with the CO + 2 ion derived from more aged OA as hydrocarbon fragments are oxidised to form organic acids (Zhang et al, 2005;Aiken et al, 2008), although m/z 44 is also a constituent of fresh smoke and has been shown to be significantly elevated at source, dependent on combustion conditions (Weimer et al, 2008;Jolleys et al, 2014). While strongly associated with saturated hydrocarbon fragments, m/z 43 can also originate from oxidised compounds such as aldehydes and ketones (Alfarra et al, 2004).…”
Section: Tracers For Combustion Conditionsmentioning
confidence: 99%
“…f 60 repre-sents the prevalence of primary combustion products such as levoglucosan and is used as an indicator for fresh BB emissions (Schneider et al, 2006;Alfarra et al, 2007). Conversely, f 44 is associated with the CO + 2 ion derived from more aged OA as hydrocarbon fragments are oxidised to form organic acids (Zhang et al, 2005;Aiken et al, 2008), although m/z 44 is also a constituent of fresh smoke and has been shown to be significantly elevated at source, dependent on combustion conditions (Weimer et al, 2008;Jolleys et al, 2014). While strongly associated with saturated hydrocarbon fragments, m/z 43 can also originate from oxidised compounds such as aldehydes and ketones (Alfarra et al, 2004).…”
Section: Tracers For Combustion Conditionsmentioning
confidence: 99%
“…The relative contributions of POA and SOA to the total OA remains an open issue as different studies report wide ranges of estimates (Kanakidou et al, 2005;Hallquist et al, 2009). Traditionally, models have tended to predict a predominance of POA over SOA (Chung and Seinfeld, 2002;Kanakidou et al, 2005;Pun et al, 2003;Vutukuru et al, 2006), but measurement studies show striking evidence of SOA dominance observed at various locations, even in heavily urbanized locations (Zhang et al, 2005de Gouw et al, 2005;Volkamer et al, 2006). Recent work has suggested that many global models are underestimating OA sources (Heald et al, 2010;Spracklen et al, 2011b) that appear to be SOA, and recent improvements in SOA modeling efforts have addressed this discrepancy (Jathar et al, 2011;Pye and Seinfeld, 2010).…”
Section: W Trivitayanurak and P J Adams: Does The Poa-soa Split Mamentioning
confidence: 99%
“…Recent work has suggested that many global models are underestimating OA sources (Heald et al, 2010;Spracklen et al, 2011b) that appear to be SOA, and recent improvements in SOA modeling efforts have addressed this discrepancy (Jathar et al, 2011;Pye and Seinfeld, 2010). To complicate the matter even further, different measurement techniques result in different SOA/OA fractions, as was the case for the Pittsburgh Air Quality Study, for which SOA/OA values were estimated to be 35-73 % (Subramanian et al, 2007;Cabada et al, 2004;Shrivastava et al, 2007;Zhang et al, 2005). Therefore, there exists great uncertainty regarding the POA-SOA split.…”
Section: W Trivitayanurak and P J Adams: Does The Poa-soa Split Mamentioning
confidence: 99%
“…The vectormatrix model in which the vector contains a factor size distribution and the matrix shows how the chemical composition of that characteristic size distribution changes with time ( Fig. 1c) would likely identify modes of submicron aerosol and the sources and processes affecting the those aerosol Zhang et al, 2005). In contrast, the vectormatrix model in which the vector contains a factor time series and the matrix shows the size dependence of that factor's chemical composition (Fig.…”
Section: Directions For Future Researchmentioning
confidence: 99%